The Role of Pshological Wellbeing and Personal Resilience towards Successful Expatriate Assignees in High Risk Countries (HRCs) - Khakimova, Nilufar; Kaur, Devinder; Singh Kartar Singh, Jugindar (International Journal of Psychosocial Rehabilitation, 2020)
Emerging growth of MNCs in high risk countries (HRCs) coupled with the growing concern of expatriates’ success (adjustment and performance) is the current highlight of research in the area of expatriate management. Despite the significant increase of global assignees, the rate of failed assignments does not appear to abate over a long period of time. A large degree of variance in expatriate performance still remains unexplained. Recent scholars have argued that individual differences should be considered as a top priority that enables expatriates to cope with stress and make sense of their environment. However, there is still a paucity of research linking individual differences and both expatriate adjustment and performance. Therefore, this paper will focus on the link between psychological wellbeing, personal resilience and expatriates’ success in HRCs which will present new insights in the area of expatriate management.